2010
DOI: 10.51347/jum.v14i2.3955
|View full text |Cite
|
Sign up to set email alerts
|

The persistence of suburban centres in Greater London: combining Conzenian and space syntax approaches

Abstract: The relationship between settlement form and the historical persistence of concentrations of diverse socio-economic activity in Greater London’s suburban centres through successive phases of rapid urban transformation is examined. Particular consideration is given to the development of three suburbs in Greater London: Barnet, South Norwood and Surbiton. Conzenian and space syntax approaches are combined within an integrated GIS environment. Both these approaches identify the historical grain of settlement form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(7 citation statements)
references
References 7 publications
0
6
0
1
Order By: Relevance
“…In their study, Kuzugil et al [2] stated that places with high integration values constitute important routes for passing tourists, while places with low integration values may prevent tourists from reaching these regions. In studies applying space syntax to visitor behavior and street networks, it was revealed that tourists prefer to walk on streets with high integration values [10,26,66,67]. It is indicated that UNESCO Standards emphasize the need to advance the decision-making process for the development and management of cities and historical sites [68].…”
Section: Discussionmentioning
confidence: 99%
“…In their study, Kuzugil et al [2] stated that places with high integration values constitute important routes for passing tourists, while places with low integration values may prevent tourists from reaching these regions. In studies applying space syntax to visitor behavior and street networks, it was revealed that tourists prefer to walk on streets with high integration values [10,26,66,67]. It is indicated that UNESCO Standards emphasize the need to advance the decision-making process for the development and management of cities and historical sites [68].…”
Section: Discussionmentioning
confidence: 99%
“…Griffiths vd. [25], Gospodini [13] ve Hillier [26,27], ziyaretçilerin davranışları ve sokak ağları üzerine mekân dizimi analizini uygulayan çalışmalar yapmışlardır. Bu çalışmalarda, turistlerin yüksek entegrasyon değerine sahip sokaklarda yürümeyi tercih ettiğini göstermektedir.…”
Section: Kent Morfolojisi Ve Mekan Dizimi Analizi (Urban Morphology A...unclassified
“…Advances in software during the past decade have paved the way for novel methods to describe, classify and represent various types of urban space through the visualisation and analysis of urban form's spatial and socioeconomic properties. Methods proposed in recent years include those developed by Griffiths et al (2010), Osmond (2010) and Hillier (1996), which their main aim is to assess the morphological bases of urban areas. Other attempts have also been made to model urban growth and analyse the spatial patterns of urban transformations using various algorithms.…”
Section: Urban Transformation Analysismentioning
confidence: 99%